On the profitability of irrigated fodder production: comparative evidence from smallholders in Koga irrigation scheme, Ethiopia - Getnet, Kindie; Haileslassie, Amare; Dessalegne, Y.; Hagos, Fitsum; Gebregziabher, Gebrehaweria (Commonwealth Scientific and Industrial Research Organisation, 2017)
Irrigated fodder production can be vitalised as a useful strategy to sustainably intensify subsistence livestock production owned and managed by smallholders and to diversify farm income through linkages to commercial livestock systems. However, uncertainty about the production and market environment of such a non-traditional commodity can be a major hindrance against commercialisation and scaling out of irrigated fodder production. This makes ex-ante analysis of profit portfolio and its determinants necessary in order to improve farmers’ investment and risk management decisions. Using a stochastic approach to farm profit analysis to account for business uncertainty, this paper simulated and compared the level and distribution of profit that smallholders in Koga irrigation scheme (Ethiopia) can generate from irrigated Rhodes grass seed and from traditional irrigated crops. The finding shows the absolute and comparative profitability of irrigated Rhodes grass seed. Though 0.19 times less profitable than irrigated onion, irrigated Rhodes grass seed is 4 times, 1.27 times, and 1.25 times more profitable than irrigated barley, irrigated wheat, and irrigated tomato, respectively. Profit from the commodity is robust to adverse business conditions such as yield reduction, cost increase, and price reduction, assuring optimism about positive financial returns from investments to expand production. Long-term business viability can be improved and farm income further stabilised through interventions targeted at fodder agronomy to enhance crop yield and at value chain development to improve market linkages and output price.